MDAD: A Special Resource for Microbe-Drug Associations - Sun, Ya-Zhou; Zhang, De-Hong; Cai, Shu-Bin; Ming, Zhong; Li, Jian-Qiang; Chen, Xing (Frontiers in Cellular and Infection Microbiology, 2018)
The human-associated microbiota is diverse and complex. It takes an essential role in human health state and behavior, and is closely related to the occurrence and development of disease. Although the diversity and distribution of microbial communities has been widely studied, little is known about the function and dynamics of microbes in human body, as well as the complex mechanisms of interaction between them and drugs, which are important for drug discovery and design. A high-quality comprehensive microbe and drug association database will be extremely beneficial to explore the relationship between them. In this article, we developed the Microbe-Drug Association Database (MDAD), a collection of clinically or experimentally supported associations between microbes and drugs, collecting 5055 entries that include 1388 drugs, 180 microbes from multiple drug databases and related publications. Moreover, we provided detailed annotations for each record including the molecular form of drugs or hyperlinks from DrugBank, microbe target information from Uniprot and the original reference links. We hope MDAD will be a useful resource for deeper understanding of microbe and drug interactions and be beneficial to drug design, disease therapy and human health.